TECHNOLOGY FOR EXTRACTING HIGH-QUALITY GRAPHITE BASED ON A COMBINATORIAL PROCESSING SCHEME - Samidinovich, Sadullayev Bakhtiyor (Journal of Geography, Regional Planning and Development, 2025)
Objective: This study aims to develop an integrated and environmentally adaptive processing technology for producing high-purity graphite suitable for advanced industrial applications. Method: A combinatorial scheme was implemented, involving multi-stage flotation enrichment, pyrometallurgical treatment at 900–1000°C, and hydrometallurgical leaching using hydrochloric acid. Results: Flotation increased the carbon content to 94%, while subsequent thermal and chemical treatments further enhanced the purity to 98.4% carbon with an ash content of only 0.74%. Comparative analysis revealed that hydrochloric acid was more effective than nitric acid in removing mineral impurities. Novelty: The study introduces a unified technological pipeline that combines flotation, thermal processing, and hydrometallurgical leaching—providing a cleaner and more sustainable alternative to conventional acid-intensive purification methods. This approach not only improves graphite quality but also reduces environmental hazards, offering practical value to the energy, nuclear, and metallurgical industries.